Laparoscopic‐assisted gastrotomy for foreign body retrieval in four dogs. Issue 2 (20th April 2020) - Gibson, Erin; Culp, William; Mayhew, Philipp; Runge, Jeffrey J; Peterson, Lindsay C; Balsa, Ingrid M; Kim, Sun Y
Abstract : Four dogs with gastric foreign bodies were treated by laparoscopic‐assisted gastrotomy. Techniques included two‐port technique (n=two dogs), single‐port with Alexis wound retractor (one) and single‐port GelSeal cap with three cannulae (one). Foreign bodies retrieved included gravel (n=two dogs), trichobezoar (one) and a ball (one). All dogs had foreign bodies successfully removed, and no complications were encountered associated with the surgical procedures. These results suggest that laparoscopic‐assisted gastrotomy is a feasible treatment for dogs with gastric foreign bodies via standard two‐port technique, single‐port with Alexis wound retractor, or single‐port with GelSeal device. The benefits of minimally invasive surgery have been well‐established for veterinary patients, and further investigation into additional uses is essential; the findings of this series highlight the importance of considering laparoscopic assistance for procedures such as gastrotomy.